PENERAPAN METODE SURVEY, QUESTION, READ, RECITE DAN REVIEW (SQ3R) UNTUK MENINGKATKAN KEMAMPUAN MEMBACA PEMAHAMAN PADA SISWA KELAS IV SD NEGERI 010 MEREMPAN HILIR KABUPATEN SIAK - Sulastri, Sulastri; Kurniaman, Otang; Noviana, Eddy (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: Low level of understanding of the reading skills of students because teachers rarely apply various learning methods, students are trained in reading comprehension through processes or stages that should have been done. Data obtained from the total number of students that add up to 20 students, which can achieve good category revealed nothing. As many as 7 students are on a category, and 10 students are in the category of less. This means that as many as 85% of students do not have the ability of reading comprehension, with the average classroom reached only 59,25. This type of research is research conducted a class act by applying the method of learning survey, question, read, recite, and review (SQ3R) which aims to improve students' reading comprehension at fourth grade students' of elementary school 010 merempan hilir siak regency. This research was carried out on the even semester academic year 2016/2017 with the subject grade IVA consisting of 12 male students and 8 female students. Before the research is done, the researchers prepare a learning device in the form of the syllabus, RPP and LKS, as well as the data collection instruments in the form of sheets, teacher observation of student observation sheet, and the problem repeats daily. After research by application method SQ3R is done, there is an increase in the average reading skills of students understanding of the base score to evaluation I daily of 6.7%, from 59.25 rose to 63.25 and cycle II happen again increased an average of 39.2% reached 82.5. The results of the data analysis activities teachers and students also experienced an increase in both the cycle. Based on the results of the research that has been done, it can be concluded that the application of the method of survey, question, read, recite, and review (SQ3R) can improve students' reading comprehension at fourth grade students' of elementary school 010 merempan hilir siak regency.Key Words: Reading, Comprehension, sq3r